Morphogenesis and bone integration of the mouse mandibular third molar - Veselá, Ivana; Lungová, Vlasta; Wells, Kirsty; Tucker, Abigail S; Radlanski, Ralf J; Míšek, Ivan; Matalová, Eva (European journal of oral sciences, 2011)
The mouse third molar (M3) develops postnatally and is thus a unique model for studying the integration of a non-mineralized tooth with mineralized bone. This study assessed the morphogenesis of the mouse M3, related to the alveolar bone, comparing M3 development with that of the first molar (M1), the most common model in odontogenesis. The mandibular M3 was evaluated from initiation to eruption by morphology and by assessing patterns of proliferation, apoptosis, osteoclast distribution, and gene expression. Three-dimensional reconstruction and explant cultures were also used. Initiation of M3 occurred perinatally, as an extension of the second molar (M2) which grew into a region of soft mesenchymal tissue above the M2, still far away from the alveolar bone. The bone-free M3 bud gradually became encapsulated by bone at the cap stage at postnatal day 3. Osteoclasts were first visible at postnatal day 4 when the M3 came into close contact with the bone. The number of osteoclasts increased from postnatal day 8 to postnatal day 12 to form a space for the growing tooth. The M3 had erupted by postnatal day 26. The M3, although smaller than the M1, passed through the same developmental stages over a similar time span but showed differences in initiation and in the timing of bone encapsulation.
Keywords: molár třetí; Animals; moláry; zubní zárodek; proliferace buněk; apoptóza; Morphogenesis; mandibula; Proliferating Cell Nuclear Antigen; techniky tkáňových kultur; Acid Phosphatase; Tooth Eruption; biologické markery; zobrazování trojrozměrné; proliferační antigen buněčného jádra; Biomarkers; hybridizace in situ; Imaging, Three-Dimensional; Molar; osteogeneze; Apoptosis; osteoblasty; odontogeneze; Osteoclasts; Hedgehog Proteins; Odontogenesis; morfogeneze; zubní kořen; Mice; Tooth Calcification; Mandible; Enamel Organ; Molar, Third; prořezávání zubů; Tooth Root; Bone Resorption; myši; osteoklasty; orgán skloviny; Tissue Culture Techniques; Tooth Germ; počítačové zpracování obrazu; kyselá fosfatasa; Osteoblasts; processus alveolaris; In Situ Hybridization; Cell Proliferation; resorpce kosti; Fibroblast Growth Factor 4; Osteogenesis; Alveolar Process; Isoenzymes; zvířata; kalcifikace zubů; proteiny hedgehog; fibroblastový růstový faktor 4; izoenzymy; Image Processing, Computer-Assisted